Men's artistic gymnastics: is the use of elastic surfaces systematic in the training process? - Marco Antonio Coelho BORTOLETO; Tiago Furtado COELHO (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract In Artistic Gymnastics, the area (the apparatus) represents the most relevant systemic component. Thus, when one strives to comprehend the internal logic of this sport, the gymnast-apparatus relationship warrants special attention. A change in the training paradigm was observed, showing that the use of Elastic Surfaces (ES) is an essential resource, due to the contemporary features of this sport, such as the hyper-valorisation of acrobatics and a greater presence of flight elements. Through a case study developed in a men's artistic gymnastics high-performance gymnasium, this study analysed the use of different ES in the training process. Although coaches recognize the importance of ES in training programs, the record of daily activities showed that this use is still limited to select equipment and is not systematic. Such difficulties are due mainly to the lack of educational programs to the development of certain specific methodologies and the non-existence of national equipment suppliers certified by International Gymnastics Federation.